SPEECH STYLE IN MALEFICEN'T MOVIE - Mulya, Sri; Mahmud, Murni (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
When people converse with one another, they utilize a variety of speech. The goal of this study was to ascertain the main character's speech pattern and how language style is used from a linguistics standpoint. This study employed a qualitative research methodology. The movie Maleficent served as the study's data source. Maleficent is a 2014 American dark fantasy adventure film directed by Robert Stromberg from a screenplay by Linda Woolverton. Loosely inspired by Charles Perrault's original fairy tale, the film is a live action retelling of Walt Disney's 1959 animated film Sleeping Beauty, and portrays the story from the perspective of the eponymous antagonist, depicting her conflicted relationship with the king and princess of a corrupt kingdom According to the data that was analyzed, Maleficent employs the formal, consultative, and casual modes. There are five kinds according to Joo's idea, but the investigation did not uncover the Frozen Style and the Intimate Style.